2017
DOI: 10.1038/ng.3753
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic reprogramming during pancreatic cancer progression links anabolic glucose metabolism to distant metastasis

Abstract: During the evolutionary progression of pancreatic ductal adenocarcinoma (PDAC), heterogeneous subclonal populations emerge that drive primary tumor growth, regional spread, distant metastasis, and patient death1–3. However, the genetics of metastases largely reflects that of the primary tumor in untreated patients, and PDAC driver mutations are shared by all subclones1. This raises the possibility than an epigenetic process might operate during metastasis. Here we detected striking epigenetic reprogramming of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
367
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(385 citation statements)
references
References 46 publications
17
367
1
Order By: Relevance
“…This mechanism appears to be distinct from our observations in PDA, since we did not observe generalized increases in chromatin accessibility associated with metastasis in this setting. Disruption of large heterochromatin domains of H3K9/H4K20 methylation has also recently been linked with PDA metastasis (McDonald et al, 2017). Within this larger body of evidence of epigenetic deregulation in metastasis, our study calls attention to alterations of the enhancer landscape as a mechanism by which tumor cells gain metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism appears to be distinct from our observations in PDA, since we did not observe generalized increases in chromatin accessibility associated with metastasis in this setting. Disruption of large heterochromatin domains of H3K9/H4K20 methylation has also recently been linked with PDA metastasis (McDonald et al, 2017). Within this larger body of evidence of epigenetic deregulation in metastasis, our study calls attention to alterations of the enhancer landscape as a mechanism by which tumor cells gain metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, small-molecules that target readers, writers, or erasers of histone modifications have shown promising therapeutic effects in mouse models of PDA by altering transcription of cancer genes (Hessmann et al, 2017). A recent study has shown that disruption of large heterochromatin domains is associated with the metastatic transition in PDA, as a consequence of aberrant oxidative pentose phosphate metabolism (McDonald et al, 2017). However, the direct functional evidence that links chromatin regulation to PDA metastasis remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that LKB1-deficiency could be a key vulnerability as DNA methyltransferase and serine metabolism inhibition reduced tumor growth 117 . A distinct line of work on the evolution of distant metastases of pancreatic ductal adenocarcinoma (PDAC) demonstrated that the oxidative branch of the pentose phosphate pathway (oxPPP) was a driving force for epigenome landscape reprogramming and the fitness of metastatic cells 118 , suggesting that targeting the oxPPP could be effective in metastatic PDAC. Together, these studies represent a few examples on how advances in our understanding of metabolic effects on epigenetics can be translated into potential therapies.…”
Section: Introductionmentioning
confidence: 99%
“…While their genomic landscape is very similar, it has appears that they had very different epigenomic reprogramming [52]. Depending on the localization, the distribution of the different histone types and modifications varies and this results in a wide modification of Phylogenetic tree illustrating the tumor evolution and intratumor heterogeneity in pancreatic adenocarcinomas (adapted from Makohon-Moore et al [47]).…”
Section: Metastasis Heterogeneitymentioning
confidence: 99%